Completely conserved VP2 residue K140 of KREMEN1-dependent enteroviruses is critical for virus-receptor interactions and viral infection - Zeyu Liu; Xue Li; Xiaohong Li; Xingyu Yan; Yuan Tian; Yue Zhao; Kexin Liu; Pei Hao; Shuye Zhang; Chao Zhang (mBio)
ABSTRACT The KREMEN1 (KRM1) protein is a cellular receptor for multiple enteroviruses that cause hand, foot, and mouth disease (HFMD), including coxsackievirus CVA2, CVA3, CVA4, CVA5, CVA6, CVA10, and CVA12. The molecular basis for the broad recognition of these viruses by the KRM1 receptor remains unclear. Here, we report the indispensable role of the completely conserved VP2 capsid protein residue K140 (designated K2140) in mediating receptor recognition and infection by CVA10 and other KRM1-dependent enteroviruses. Residue K2140 not only facilitates receptor recognition, cell attachment, and infection of CVA10 but also contributes to CVA10 pathogenicity in vivo. Notably, residue K2140 is completely conserved in all strains of the KRM1-dependent enteroviruses. Mutational analysis confirms the importance of K2140 for infection by CVA2–CVA6, and CVA12. Moreover, CVA8, an enterovirus for which the cellular receptor has not yet been identified, also possesses the conserved K2140 residue. We experimentally demonstrate that CVA8 utilizes KRM1 as its receptor, with K2140 being essential for viral infection. Additionally, residue D90 of KRM1 engages with residue K2140 and plays a crucial role in KRM1-mediated enterovirus infections. Collectively, our findings underscore the significance of the absolutely conserved K2140 residue in receptor interactions and infection of all KRM1-binding enteroviruses, providing novel insights into the molecular basis of enterovirus infection and informing the development of broad-spectrum therapies against HFMD.IMPORTANCEHand, foot, and mouth disease (HFMD) annually affects millions of children worldwide. HFMD is caused by various enteroviruses, such as coxsackieviruses CVA6, CVA16, CVA10, and enterovirus 71 (EV-A71). Licensed inactivated EV-A71 vaccines do not provide cross-protection against other enteroviruses. There are no drugs specifically for HFMD. KREMEN1 (KRM1) serves as the cellular receptor for many HFMD-related enteroviruses, including CVA2–CVA6, CVA10, and CVA12. However, the molecular basis for broad recognition of these enteroviruses by the KRM1 receptor remains elusive. Here, we report that VP2 residue K140 (K2140) is completely conserved among all KRM1-dependent enteroviruses and is essential for virus-receptor binding and viral infection by interacting with residue D90 of KRM1. Overall, our findings provide a deeper understanding of the molecular basis of KRM1-dependent enterovirus infection in vitro and in vivo and may contribute to the development of broad-spectrum anti-enterovirus vaccines and treatments.